PERANCANGAN MESIN PEMIPIH DAN PEMOTONGAN ADONAN MIE PENGGERAK MOTOR LISTRIK - Ega Prasetya Hidayat; Januar Moch Izhardaz; Joshua Raharjo; Sobron Yamin Lubis (Program Studi Teknik Mesin Universitas Tarumanagara, 2022)
Noodles are foods that we often encounter wherever they are, such as at street vendors, restaurants, and even instant food. This noodle flattening and cutting machine is a tool that is used to make it easier for producers or street vendors to make it easier to print their own noodles. Based on this, this design was carried out to produce a flattening machine design and cutting noodle dough using an electric motor. The design of the flattening and dough cutting machine is carried out by calculation and drawn using Autodesk Fusion 360 software. From the calculation, it is obtained that the electric motor used is 0.5 HP with a rotation of 1400 r/min. The motor drives 4 pulleys that are connected to a belt connected to each other, and has an efficiency value in the transmission system of = 95%